Glutathione in Brain Disorders and Aging - Igor Y. Iskusnykh; Anastasia A. Zakharova; Dhruba Pathak (Molecules, 2022)
Glutathione is a remarkably functional molecule with diverse features, which include being an antioxidant, a regulator of DNA synthesis and repair, a protector of thiol groups in proteins, a stabilizer of cell membranes, and a detoxifier of xenobiotics. Glutathione exists in two states—oxidized and reduced. Under normal physiological conditions of cellular homeostasis, glutathione remains primarily in its reduced form. However, many metabolic pathways involve oxidization of glutathione, resulting in an imbalance in cellular homeostasis. Impairment of glutathione function in the brain is linked to loss of neurons during the aging process or as the result of neurological diseases such as Huntington’s disease, Parkinson’s disease, stroke, and Alzheimer’s disease. The exact mechanisms through which glutathione regulates brain metabolism are not well understood. In this review, we will highlight the common signaling cascades that regulate glutathione in neurons and glia, its functions as a neuronal regulator in homeostasis and metabolism, and finally a mechanistic recapitulation of glutathione signaling. Together, these will put glutathione’s role in normal aging and neurological disorders development into perspective.